BOLT FATIGUE RELIABILITY IN SBARCH BRIDGE USING WEIGH-IN-MOTION (WIM) DATA - Aulia, Rahmi
SBArch Bridge is a double composite bridge that filled with concrete in arch steel section. The arch shape is a combination of U-shaped section and I-shaped section. This bridge structure has bolted joints that connect several girder segments. The connections contained in the bridge have a factor of stress concentration and structure that is not continuous. Thus, the connections need to be considered well against fatigue hazards by avoiding unnecessary stress concentrations. This study will evaluate the level of fatigue reliability that occurs in Bolts by using a moving vehicle load or weigh-in-motion (WIM). This study begins by checking the fatigue limits of bridge design according to AASHTO, SNI and Eurocode. Record data conducted by the Center For Research and Development of Roads and Bridges (PUSJATAN) on the north coast of Kendal, Central Java was used in this study. The vehicle load data used in this study is the result of measuring WIM vehicle load with a measurement duration of 5 (five) weeks in the period from November 1, 2020 to December 5, 2020. WIM data measured by PUSJATAN has a dynamic factor of 1.1 is then applied to the model with the number of simulation motorcade of 1301 vehicles. The number of cycles that occur on the bridge is then projected according to the WIM data. This study uses SBArch Bridge that located on Krian Legundi Bunder Manyar Toll Road as the object of research. This bridge has a total length of 167.4 m, 2 lanes with a width of each lane of 16.15 m. The bridge is modeled with SAP2000. From the analysis of the structure obtained bending moment and shear forces that occur at the connection point. After collecting the data then processed to obtain stress in the bolt connection due to random vehicle load. Then processed statistically stress at the bolt connection to obtain statistical parameters of the bolt stress distribution. The SN curve used in determining the level of fatigue reliability of bolts is obtained from several literatures. This curve is grouped into two curves for bolts with shear plane locations in threaded and not in threaded. The bolts used in the study used F10T quality bolts or equivalent to Grade 10.9 or A490. The analysis results showed that the distribution of stress range on bolt Detail 11 follows the beta distribution with the parameter ?1=3.3892, ?2=10.1377, a=6.1309 dan b=31.6996 and mean stress 83.3733 MPa. Assuming that vehicles crossing the SBArch Bridge are at a 25% reduction from the Kendal Pantura Road, the risk of fatigue failure in bolts is 1.05E-08 or a bolt fatigue safety index of 5.60 at the 50-year life design. The value is still at the safe limit, where the safety index according to Eurocode for 50-year life design is 4.30. On the SBArch Bridge, the bolt connection is very reliable in resisting the fatigue force that occurs.